Sustainability of urban recreational waterfront development in Colombo urban area, Sri Lanka - D.U., Rathnaweera; K.G.P.K., Weerakoon (Penerbit Universiti Kebangsaan Malaysia, 2021)
Cities in the twenty-first century recognized water's worth as a symbolic and spatial interpretive element. For city people who live in congested urban environments, waterfront areas provide excellent outdoor recreation and leisure opportunities. It revitalizes and arranges urban environments while avoiding the creation of spatial boundaries. It increases the value of urban environments and can help individuals visualize a specific image in their heads. The development of waterfront areas allows for the proper integration of human activities and agglomerations in an increasingly vulnerable and deteriorating environment. Consequently, the sustainability of waterfront development is vital for urban planning. Colombo urban area of Sri Lanka focusing on recreational waterfront development projects in recent years. Now is the time to pay attention to assessing the sustainability of these projects. This research evaluated this gap, with the aim of evaluating the sustainability of urban recreational waterfront development initiatives in the Colombo Urban Area. Primary and secondary data sources are used in a qualitative research approach. Observations and interviews are used to gather primary data. Using a judgmental sampling technique, structured interviews were conducted with professionals involved in Sri Lankan urban recreational waterfront development projects. Content analysis was used as a method of qualitative data analysis. The study outcome discovered that six environmental factors, three economic factors, and seven social factors contribute to the long-term sustainability of urban recreational waterfront development projects in Sri Lanka. The paper concludes with recommendations on sustainable measures in Colombo waterfront development and a well-designed waterfront that respects community aspirations.